Tempo ético e tempo histórico: a reapropriação heideggeriana do kairos como Augenblick - Santos, Gilfranco Lucena dos (2011)
This work aims to show the transformation of Aristotle s predicative comprehension of kairos concept in Heidegger s existential comprehension of the same one. Since Aristotle s definition of kairo,j is the Good, said in according to category of time (when), Heidegger has not anymore interpreted the same concept in predicative sense, but has integrated the phenomenon of kairo,j in his Existential Analytics as an instant (Augenblick), in what the existence freely open up to History as own historicity. It will be saw that, this transformation of the phenomenon of kairo,j from a predicative sense to an existential and historical sense is the ground to an Ethics, that could be called Ethics of Historical Freedom.